Antigenic relationships among human pathogenic Orientia tsutsugamushi isolates from Thailand - James, S; Blacksell, S; Nawtaisong, P; Tanganuchitcharnchai, A; Smith, D; Day, N; Paris, D (Public Library of Science, 2016)
Scrub typhus is a common cause of undiagnosed febrile illness in certain tropical regions, but can be easily treated with antibiotics. The causative agent, Orientia tsutsugamushi, is antigenically variable which complicates diagnosis and efforts towards vaccine development.This study aimed to dissect the antigenic and genetic relatedness of O. tsutsugamushi strains and investigate sero-diagnostic reactivities by titrating individual patient sera against their O. tsutsugamushi isolates (whole-cell antigen preparation), in homologous and heterologous serum-isolate pairs from the same endemic region in NE Thailand. The indirect immunofluorescence assay was used to titrate Orientia tsutsugamushi isolates and human sera, and a mathematical technique, antigenic cartography, was applied to these data to visualise the antigenic differences and cross-reactivity between strains and sera. No functional or antigen-specific analyses were performed. The antigenic variation found in clinical isolates was much less pronounced than the genetic differences found in the 56kDa type-specific antigen genes. The Karp-like sera were more broadly reactive than the Gilliam-like sera.Antigenic cartography worked well with scrub typhus indirect immunofluorescence titres. The data from humoral responses suggest that a Karp-like strain would provide broader antibody cross-reactivity than a Gilliam-like strain. Although previous exposure to O. tsutsugamushi could not be ruled out, scrub typhus patient serum antibody responses were characterised by strong homologous, but weak heterologous antibody titres, with little evidence for cross-reactivity by Gilliam-like sera, but a broader response from some Karp-like sera. This work highlights the importance of antigenic variation in O. tsutsugamushi diagnosis and determination of new serotypes.